The burden of taxation on sixteenth-century London - Archer, I (Cambridge University Press, 2001)
This article seeks to establish the burden of direct taxation in the city of London in the sixteenth century. Previous discussions have been confined to the yield of parliamentary subsidies which cannot give a full picture because of the way responsibility for equipping military levies was increasingly devolved on to the locality. Estimates of the costs of the various additional military levies are therefore made. Innovations in parliamentary taxation enabled the crown to levy extraordinary sums in the 1540s, but they required a level of intervention by the privy council which Elizabeth's government was not prepared to make. The subsidy performed especially badly in London in the later sixteenth century. Local military rates compensated to some extent, but tax levels in real terms were very much lower in the 1590s than the 1540s. Nevertheless taxation was becoming increasingly regressive, which helps to explain the greater level of complaint in the 1590s.